2015
DOI: 10.1590/0100-69912015001003
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of the treatment of earlobe keloids with triamcinolone injections, surgical resection, and local pressure

Abstract: the combination of infiltration TCN month to 20 mg/mL (1.2mg to 2.0mg per mm3 TCN injury), surgical excision and pressure application device is effective for treatment of keloid ear lobe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
(15 reference statements)
0
22
0
Order By: Relevance
“…Hypertrophic scar (HS) is a very common cutaneous complication following dermal wound, especially after severe burns78. Currently, there are a variety of therapeutic options for treatment of HS including pressure therapy (PT), silicone-based products, intralesional corticosteroids, laser therapy, bleomycin, fluorouracil, topical imiquimod and surgical excision2910. However, no ideal or all-purpose method of scar control exists and HS management remains a problematic challenge for both patients and health care providers511.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertrophic scar (HS) is a very common cutaneous complication following dermal wound, especially after severe burns78. Currently, there are a variety of therapeutic options for treatment of HS including pressure therapy (PT), silicone-based products, intralesional corticosteroids, laser therapy, bleomycin, fluorouracil, topical imiquimod and surgical excision2910. However, no ideal or all-purpose method of scar control exists and HS management remains a problematic challenge for both patients and health care providers511.…”
mentioning
confidence: 99%
“…Secondly, the effectiveness of PT in HS prevention and treatment remains controversial. Some studies showed that PT could promote HS maturation, restrain its formation, improve its appearance, minimize itch and pain1020. However, others indicated that PT not only left the ultimate outcome of burn wounds unchanged but also increased the incidence of overheating, pruritus, blistering, wound breakdown and abnormal bone growth718.…”
mentioning
confidence: 99%
“…20mg/ml reduces the side effects of TAC without jeopardizing the efficacy. [16][17][18] In this study, majority of the subjects were in the age group <30 years; males being slightly more than females. Uzair et al and Ahuja et al also observed predominance of keloid in the younger age group.…”
Section: Resultsmentioning
confidence: 67%
“…[7] However, anaphylactic reactions have been observed due to triamcinolone injections. [8] Adjuvant radiotherapy resulted in one study to a reduced recurrence rate of 4%. [9] Short-term adverse effects were not observed.…”
Section: Discussionmentioning
confidence: 99%